Pengembangan Media Interaktif Pengembangan Media Interaktif Berbasis Game Edukasi dalam Meningkatkan Kreativitas Guru Sekolah Dasar di Masa Pandemi Covid-19 - Aminuddin, Fattachul Huda; Djauhari, Teuku D; M.Pd, Merty Megawati (JITCE (Journal of Information Technology and Computer Engineering), 2021)
The presence of the Covid-19 Virus in the world has not only changed the learning culture, but has become a new challenge in developing teacher creativity in the teaching and learning process. This conventional learning pattern that has evolved into technology-based distance learning requires teachers to be able to adapt and adapt to the limited learning needs of students during the pandemic. Digital technology tools are currently very developed, but they are enough to help educators to adapt to the diverse learning needs of today's students. So it is necessary to use the right learning media in carrying out learning during the pandemic. This training aims to train abilities and skills in increasing the creativity of teachers in using interactive learning media during the pandemic using the Quizizz platform. Quizizz is an interactive game-based online platform that can be used in a fun teaching and learning process during the Covid-19 pandemic by utilizing an Android smartphone. The method used is the lecture method and interactive training by involving the teacher as a simulation model.